Caracterización Ecológica Cuantitativa De La Vegetación En Sitios De La Costa Central Del Golfo En El Desierto Sonorense - Carlos Hugo Alcalá Galván; José Enrique Maytorena Gaytán; Ramón Héctor Barraza Guardado; Edgar Omar Rueda-Puente (European Scientific Journal, ESJ, 2016)
The Central Gulf Coast, subdivision of the Sonoran Desert, requires urgent actions to ecological restoration and development of sustainable alternatives to promote the generation of economic benefits in a manner consistent with the conservation of natural resources. Four sites were selected in the coastal region of the municipality of Hermosillo between 28°42'04" and 28°52'24" North and 111°45'39" and 111°56'48" West. Sites are representative of the various plant associations with variants in soil structure, topography and intensities of use. General plant diversity, plant density, height and canopy cover from shrub/tree plants, and basal cover from herbaceous plants were evaluated at each site. Species richness indices, equity and diversity among plant communities were compared. Major plant associations were identified as 1) Sarcocaulescent scrub, 2) Halophytes Communities, 3) Arbo-crasicaulescent scrub, and 4) Arbo-suffrutescent scrub. Sixty five plant species in 26 families were identified. Families with higher number of species were Cactaceae (12), Euphorbiaceae (7), Fabaceae (7) and Malvaceae (5). Species richness and diversity indices indicated differences between sites. Values of relative importance are identified among plant associations for subsequent analysis of productive and ecological trends as well as for the assessment of wildlife diversity and population parameters associated to each condition of the vegetation. This work is aimed to generate integral models for identifying feasibility and setting priorities for ecological restoration practices in the Sonoran Desert.